2010
DOI: 10.1007/s11274-009-0304-z
|View full text |Cite
|
Sign up to set email alerts
|

One-procedure synthesis of capsiate from capsaicin by lipase-catalyzed dynamic transacylation

Abstract: Capsiate has a structure similar to capsaicin but no oral pungency. Furthermore, capsiate displayed antioxidant activity and inhibited angiogenesis and vascular permeability, and therefore, showed potential as a medicine and food supplement. Capsaicin is now commercially available, however capsiate is scarcely present in natural foods. We investigated the direct enzymatic conversion of a capsaicinoid to a capsinoid. It was observed that the rate of lipase-catalyzed acylation of vanillyl alcohol with nonanoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Acetylated dihydrocapsiate (21) was obtained in good yield without hydrolysis or transesterification of the 4-acetoxy group. Hydroxyphenylalkyl alkanoate (23,24) and ester compounds with an inverse chemical structure compared to CSNs (25,26) were obtained in good yield under similar reaction conditions. [28][29][30][31] Note that an aliphatic ester linkage was selectively constructed in every reaction in the presence of phenol functionality.…”
Section: Synthesis Of Derivatives Of Dihydrocapsiate (Dct 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylated dihydrocapsiate (21) was obtained in good yield without hydrolysis or transesterification of the 4-acetoxy group. Hydroxyphenylalkyl alkanoate (23,24) and ester compounds with an inverse chemical structure compared to CSNs (25,26) were obtained in good yield under similar reaction conditions. [28][29][30][31] Note that an aliphatic ester linkage was selectively constructed in every reaction in the presence of phenol functionality.…”
Section: Synthesis Of Derivatives Of Dihydrocapsiate (Dct 2)mentioning
confidence: 99%
“…As an example of enzymatic synthesis, the direct conversion of capsaicinoids to CSNs by lipase-catalyzed alcoholysis-type transacylation was reported by Castillo et al and Ishihara et al; however, these methods require considerable amounts of pure capsaicinoids as an acyl donor. 23,24) Another example of condensation of VOH (8) with a fatty acid or a fatty acid methyl ester using the immobilized enzyme Novozym 435 (Novozymes, Denmark), a kind of lipase, in acetone was reported by Kobata et al 25,26) ; however, since the reaction using an enzyme is an equilibrium reaction, the conversion yield of the products was approximately 70-80%, even after long durations of reaction time or by addition of a dehydrating agent such as molecular sieves. Therefore, the equilibrium must shift to the products in some way to improve the yield.…”
mentioning
confidence: 99%
“…This is because substrates remove excess water from the immediate vicinity of the enzyme, hence limiting its overall conformational mobility. Ishihara et al [116] studied the efect of temperature on vanillyl alcohol acylation with nonanoic acid to give vanillyl nonanoate in n-hexane solvent medium. The authors found that the optimum temperature for enzymatic acylation was 70°C.…”
Section: Reaction Temperaturementioning
confidence: 99%
“…Generally, its application is oriented toward the speciic detection and potential identiication of chemicals in the presence of other chemicals (in a complex mixture). LC-MS has been used for the structural characterization of lipids and phenolic lipids [10,116].…”
Section: Analysis and Characterization Of Phenolic Lipidsmentioning
confidence: 99%
“…A large body of evidence speaks in favour of enzyme-mediated production of capsinoids. So far, Novozyme 435 has been most extensively used (Ishihara, Kwon, Masuoka, Nakajima, & Hamada, 2010;Kobata et al, 1999). However, the high cost of this catalyst imposes the necessity for alternative approaches (Chang et al, 2014;Zhao, Herbst, Niemeyer, & He, 2015).…”
Section: Introductionmentioning
confidence: 99%